"Drunk in Love": The Portrayal of Risk Behavior in Music Lyrics. Issue 10 (2nd October 2016) - Holody, Kyle J.; Anderson, Christina; Craig, Clay; Flynn, Mark
Abstract : The current study investigated the prevalence of multiple risk behaviors in popular music lyrics as well as the contexts within which they occur. We conducted a content analysis of the top 20 Billboard songs from 2009 to 2013 in the genres of rap, country, adult contemporary, rock, R&B/hip-hop, and pop, coding for the presence of alcohol, marijuana, nonmarijuana drugs, and sex as well as the contexts intoxication, binging/addiction, partying/socializing, disregard for consequences, and emotional states. The contexts relationship status and degradation were also coded for when sex was present. Of the 600 songs, 212 mentioned sexual behaviors, which were most frequent in rap and R&B/hip-hop. Alcohol was the next most frequent risk behavior, again with greatest mention in rap and R&B/hip-hop. Alcohol, marijuana, and nonmarijuana drugs were most often associated with positive emotions, and sex was most often described within the context of casual relationships. Alcohol and sex were associated with disregard for consequences most often in 2011, when the "you only live once" motto was most popular. These findings are concerning because exposure to popular music is associated with increased risk behaviors for adolescents and young adults, who are the greatest consumers of music.